The Influence of Fraud Hexagon Theory in Detecting Financial Statement Fraud Using The Dechow F-Score Model (Empirical Study on Technology Sector Companies Listed on The Indonesia Stock Exchange for The Period 2021-2024) - Katrien Dwie. AF; Sri Rahayu; Yulisman Yulisman (Siber Nusantara Research, 2026)
This study analyzes the influence of the Fraud Hexagon Theory in detecting financial statement fraud using the Dechow F-Score model on technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The six elements examined are stimulus (external pressure), capability (change in director), collusion (government project cooperation), opportunity (ineffective monitoring), rationalization (change in auditor), and ego (CEO picture ratio). This study employs a quantitative method with multiple linear regression analysis processed using IBM SPSS Statistics 26. The research sample consists of 28 technology companies with 112 observations over four years, reduced to 107 after outlier removal. The results show that simultaneously all Fraud Hexagon elements significantly influence financial statement fraud. Partially, stimulus (external pressure) and opportunity (ineffective monitoring) significantly influence financial statement fraud, while capability, collusion, rationalization, and ego do not significantly influence financial statement fraud.